2012
DOI: 10.1021/jp3032034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molecular Conformation and Polarizable Embedding for One- and Two-Photon Absorption of Disperse Orange 3 in Solution

Abstract: Solvent effects on the one- and two-photon absorption (1PA and 2PA) of disperse orange 3 (DO3) in dimethyl sulfoxide (DMSO) are studied using a discrete polarizable embedding (PE) response theory. The scheme comprises a quantum region containing the chromophore and an atomically granulated classical region for the solvent accounting for full interactions within and between the two regions. Either classical molecular dynamics (MD) or hybrid Car-Parrinello (CP) quantum/classical (QM/MM) molecular dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 65 publications
2
44
0
1
Order By: Relevance
“…Such effects, including both explicit and bulk interactions, which have been included in several previous studies of absorption and emission processes, have been demonstrated to be important. 46,49,101,102 The RRS spectrum (Figure 4b) shows good agreement with the experimental spectrum. The four most prominent features (528, 990, 1398, and 1505 cm −1 ) are vibronically coupled to the electronic transition, and this is captured in the simulation.…”
Section: Optical Processes Of the Phenoxyl Radicalsupporting
confidence: 67%
See 1 more Smart Citation
“…Such effects, including both explicit and bulk interactions, which have been included in several previous studies of absorption and emission processes, have been demonstrated to be important. 46,49,101,102 The RRS spectrum (Figure 4b) shows good agreement with the experimental spectrum. The four most prominent features (528, 990, 1398, and 1505 cm −1 ) are vibronically coupled to the electronic transition, and this is captured in the simulation.…”
Section: Optical Processes Of the Phenoxyl Radicalsupporting
confidence: 67%
“…While the simulations presented here neglect environmental effects, such as implicit or explicit solvation, this only has a small effect on the results presented in this section. It should be stressed that in situations where simulated results are compared with experiments measured in polar solvents or where environmental interactions are important, solvation effects generally must be included for accurate results 46,101,102. …”
mentioning
confidence: 99%
“…30,32,36,39 What is usually done, however, is choosing a single empirical parameter for G, often chosen to be 0.1 eV, 13,14,18,21,22,28,29,37,38 but also other broadening factors have been used, usually taken from the broadening of a specific peak in an experimental spectrum. 30,32,36,39 What is usually done, however, is choosing a single empirical parameter for G, often chosen to be 0.1 eV, 13,14,18,21,22,28,29,37,38 but also other broadening factors have been used, usually taken from the broadening of a specific peak in an experimental spectrum.…”
Section: The Lineshape Functionmentioning
confidence: 99%
“…19,21 This corresponds to an experimental setup with two laser sources (a so-called doublebeam experiment 41 ), thus in principle allowing for two photons with different energies. [30][31][32][33]39,42,43 In fact, the photon dissipation rate is in this case twice the calculated twophoton absorption rate because two photons together excite the molecule. [30][31][32][33]39,42,43 In fact, the photon dissipation rate is in this case twice the calculated twophoton absorption rate because two photons together excite the molecule.…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation